Development and characterization of a novel nanoemulsion drug-delivery system for potential application in oral delivery of protein drugs - Sun H (Dove Medical Press, 2012)
Hongwu Sun,1,* Kaiyun Liu,1,* Wei Liu,1 Wenxiu Wang,2 Chunliang Guo,1 Bin Tang,1 Jiang Gu,1 Jinyong Zhang,1 Haibo Li,1 Xuhu Mao,1 Quanming Zou,1 Hao Zeng11National Engineering Research Center for Immunological Products, Third Military Medical University, Chongqing, China; 2Key Lab of Preventive Veterinary Science and Animal Biological Technology, Shandong Binzhou Animal Science and Veterinary Medicine Institute, Binzhou, China *These authors contributed equally to this work.Background: The stability of protein drugs remains one of the key hurdles to their success in the market. The aim of the present study was to design a novel nanoemulsion drug-delivery system (NEDDS) that would encapsulate a standard-model protein drug – bovine serum albumin (BSA) – to improve drug stability.Methods: The BSA NEDDS was prepared using a phase-inversion method and pseudoternary phase diagrams. The following characteristics were studied: morphology, size, zeta potential, drug loading, and encapsulation efficiency. We also investigated the stability of the BSA NEDDS, bioactivity of BSA encapsulated within the NEDDS, the integrity of the primary, secondary, and tertiary structures, and specificity.Results: The BSA NEDDS consisted of Cremophor EL-35, propylene glycol, isopropyl myristate, and normal saline. The average particle diameter of the BSA NEDDS was about 21.8 nm, and the system showed a high encapsulation efficiency (>90%) and an adequate drug-loading capacity (45 mg/mL). The thermodynamic stability of the system was investigated at different temperatures and pH levels and in room-temperature conditions for 180 days. BSA NEDDS showed good structural integrity and specificity for the primary, secondary, and tertiary structures, and good bioactivity of the loaded BSA.Conclusions: BSA NEDDS showed the properties of a good nanoemulsion-delivery system. NEDDS can greatly enhance the stability of the protein drug BSA while maintaining high levels of drug bioactivity, good specificity, and integrity of the primary, secondary, and tertiary protein structures. These findings indicate that the nanoemulsion is a potential formulation for oral administration of protein drugs.Keywords: nanoemulsion, drug-delivery system, protein drug, oral administration, stability